Brain-behavior correlates of rhythmic timing and auditory-motor synchronization in children with developmental coordination disorder: an EEG study - Pranjić, Marija; Leung, Jason; Tam, Ka Lun; Polatajko, Helene; Welsh, Timothy; Chau, Tom; Thaut, Michael (Frontiers in Human Neuroscience, 2025)
Vulnerabilities in motor control and sensorimotor timing are hallmarks of developmental coordination disorder (DCD). Although the positive effects of rhythmic entrainment on motor performance have been demonstrated in adults with movement disorders, interactions between auditory and motor systems have not been well characterized in children with DCD. We employed neuropsychological tests, caregiver reports, adaptive psychophysical procedures, finger-tapping paradigms, and electroencephalography (EEG) recordings to determine whether children with DCD have auditory-perceptual difficulties, whether rhythmic auditory cues can improve their motor performance, and whether extensive musical training contributes to enhanced auditory-motor abilities. Thirty-four children aged 7–11 years participated, including children with DCD and typically developing children with and without musical training. As hypothesized, children with DCD exhibited difficulties in rhythmic timing in both auditory-perceptual and motor tasks, especially compared to typically developing children with musical training. Notably, rhythmic auditory stimuli significantly improved motor performance across groups, which was linked to increased beta power and reduced functional connectivity in the ipsilateral fronto-central network compared to unpaced movements. Moreover, children with musical training consistently outperformed their DCD and TD peers across tasks and showed greater interhemispheric connectivity during auditory-motor synchronization, suggesting that rhythmic skills can be enhanced through practice. Our findings provide compelling evidence for the use of individually tailored auditory/rhythm-based interventions in children with DCD and highlight the positive effects of music education on auditory-motor development. Given the strong association between rhythm perception and movement, future studies should continue to investigate the link between auditory and motor skills to identify the profiles of children who are most likely to benefit from such interventions.